Impact of the expression of epidermal growth factor, transforming growth factor alpha, and epidermal growth factor receptor on the prognosis of superficial bladder cancer - (:unkn) unknown (CAHNERS PUBL CO, 1998)
Objectives. To investigate the correlation of epidermal growth factor receptor (EGFR) expression and its ligands EGF and transforming growth factor-alpha (TGF-alpha) with disease outcome in a cohort of patients with superficial bladder cancer. Methods. Tumor samples of 21 patients with transitional cell carcinoma of the bladder were analyzed by immunohistochemistry for expression of EGFR, EGF, and TGF-alpha. Disease-related events were recorded during a routine clinical follow-up and analyzed for possible correlation with the expression status of the above-mentioned proteins. Results. All Stage pT1 transitional cell carcinomas expressed EGFR, and IO of 21 (48%) tumors showed focal areas of strong EGF and/or TGF-alpha expression. Of these, 80% with EGF positivity (8 of 10) had recurrences, whereas only 9% of patients without EGF staining (1 of 11) did so. The same pattern was observed with TGF-alpha. A strong association was confirmed between EGF/TGF-alpha positivity and tumor recurrence (P<0.005). We also found that EGF and TGF-alpha were expressed in stroma and/or around the vessels of tumor tissue in 48% and 38% of the tumors, respectively. No association was found between the recurrence rate/vascular invasion and the stromal/vascular wall expression of the growth factors. Conclusions. Expression of EGF and TGF-alpha is correlated with tumor recurrence. Also, there is the ability of vessel walls to express EGF and TGF-alpha in superficial bladder cancer. Further clarification of the impact of this expression on angioinvasion of tumor cells may be helpful in understanding the nature of local invasion and metastasis. (C) 1998, Elsevier Science Inc. All rights reserved.
Keywords: TRANSITIONAL CELL-CARCINOMA; PROSTATE